2005
DOI: 10.1002/ejic.200500210
|View full text |Cite
|
Sign up to set email alerts
|

Is the Aromatic Fragment of Piano‐Stool Ruthenium Compounds an Essential Feature for Anticancer Activity? The Development of New RuII‐[9]aneS3 Analogues

Abstract: (9) [PTA = 1,3,5-triaza-7-phosphaadamantane; enac = 1,2-bis-(isopropyleneimino)ethane; OTf = CF 3 SO 3 -] were prepared from Ru-[9]aneS 3 -dmso precursors and structurally characterized, both in solution and in the solid state by X-ray crystallography. Some of them are analogs of known cytotoxic organometallic Ru II -(η 6 -arene) and Ru II -(η 5 -cyclopentadienyl) compounds, in which the aromatic fragment is replaced by the sulfur macrocycle 1,4,7-trithiacyclononane, while the rest of the coordination sphere i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 44 publications
(56 reference statements)
8
115
0
Order By: Relevance
“…After 20 min of irradiation at 420 nm (Fig. 2B) [15] and by the appearance of free pyridine peaks in the 1 H spectrum. These results are in agreement with the reported observations for analogue piano-stool ruthenium complexes [5].…”
Section: Dark Stability and Photochemical Behavior Of 1-3 In Aqueous mentioning
confidence: 95%
See 2 more Smart Citations
“…After 20 min of irradiation at 420 nm (Fig. 2B) [15] and by the appearance of free pyridine peaks in the 1 H spectrum. These results are in agreement with the reported observations for analogue piano-stool ruthenium complexes [5].…”
Section: Dark Stability and Photochemical Behavior Of 1-3 In Aqueous mentioning
confidence: 95%
“…S4). 6 ], which gave the same aqua species 2a upon release of the Cl ligand [15,16]. Interestingly, resonances for coordinated py in 2 could still be seen after 60 min of irradiation, indicating that the photo-induced ligand release was not complete (92% from NMR signal integration).…”
Section: Dark Stability and Photochemical Behavior Of 1-3 In Aqueous mentioning
confidence: 97%
See 1 more Smart Citation
“…Essentially, the availability of solvated ions in general and aqua ions in particular made this possible (Scheme 4). [47][48][49][50] Scheme 4. The prototypical behaviour of [(…”
Section: Hydrated Organometallic Compoundsmentioning
confidence: 99%
“…It has been found that a structurally diverse range of compounds all exhibit interesting properties. For example, a wide range of arenes can be tolerated and the arene can even be replaced by cyclopentadienyl, pentamethylcyclopentadienyl [6] or the sulphur macrocycle 1,4,7-trithiacyclononane without affecting the in vitro activity significantly [7]. It has even been found that some rhodium and osmium analogues, evaluated in HT29 colon carcinoma, A549 lung carcinoma and T47D breast carcinoma cell lines in vitro, display activities that are not too dissimilar from the related ruthenium(II)-arene complexes [8].…”
Section: Introductionmentioning
confidence: 99%